Reconstructing the Textbook Writing Syllabus Through Goal-Oriented Evaluation and Outcome-Based Education Integration - Wagiran; Wati Istanti; Qurota Ayu Neina; Arum Yuliya Lestari; Qin Weifen; Amelia Novitasari (UIN Raden Mas Said Surakarta, Indonesia, 2026)
This study aims to reconstruct the Semester Learning Plan (RPS) for the Textbook Writing course through the integration of a goal-oriented evaluation model with the Outcome-Based Education (OBE) approach. The main issue addressed is the lack of optimal alignment between learning outcomes, the learning process, and the assessment system in the previously used RPS. This study employs a qualitative approach using an evaluative research method. Data were collected through document analysis and focus group discussions (FGDs). Data analysis was conducted through the stages of data reduction, categorisation, interpretation, and drawing conclusions. The research results indicate that the reconstruction of the RPS yields significant improvements in the formulation of CPMK based on Higher-Order Thinking Skills (HOTS), the alignment of CPL–CPMK–Sub-CPMK, the implementation of project-based learning, and the strengthening of authentic assessment. Quality assessment shows that the average quality score of the RPS increased from 1.8 (low category) to 3.84 (very good category), with the sharpest gains recorded in the PjBL indicator (from 1.5 to 4.0) and CPL–CPMK alignment (from 1.5 to 3.7). The integration of a goal-oriented evaluation model ensures the achievement of measurable and systematic learning outcomes within the OBE framework. The novelty of this study lies in its integrative model, which combines goal-oriented evaluation, constructive alignment, and Project-Based Learning into a single reconstruction framework for a product-based course, an approach that has not been jointly addressed in previous studies. Consequently, the reconstructed RPS is more relevant, systematic, and ready to support project-based learning oriented towards Outcome-Based Education. Penelitian ini bertujuan untuk merekonstruksi Rencana Pembelajaran Semester (RPS) mata kuliah Penulisan Buku Ajar melalui integrasi model evaluasi goal-oriented dengan pendekatan Outcome-Based Education (OBE). Masalah utama yang dikaji adalah belum optimalnya keselarasan antara capaian pembelajaran, proses pembelajaran, dan sistem penilaian pada RPS yang digunakan sebelumnya. Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian evaluatif. Data dikumpulkan melalui analisis dokumen dan focus group discussion (FGD), kemudian dianalisis melalui tahap reduksi data, kategorisasi, interpretasi, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa rekonstruksi RPS menghasilkan peningkatan signifikan dalam perumusan CPMK berbasis Higher-Order Thinking Skills (HOTS), keselarasan CPL–CPMK–Sub-CPMK, penerapan pembelajaran berbasis proyek, serta penguatan asesmen autentik. Hasil penilaian kualitas menunjukkan skor rata-rata RPS meningkat dari 1,8 (kategori rendah) menjadi 3,84 (kategori sangat baik), dengan peningkatan tertinggi pada indikator PjBL (dari 1,5 menjadi 4,0) dan keselarasan CPL–CPMK (dari 1,5 menjadi 3,7). Integrasi model evaluasi goal-oriented menjamin tercapainya capaian pembelajaran yang terukur dan sistematis dalam kerangka OBE. Kebaruan penelitian ini terletak pada model integratif yang menggabungkan evaluasi goal-oriented, constructive alignment, dan Project-Based Learning dalam satu kerangka rekonstruksi untuk mata kuliah yang berorientasi produk, yang belum banyak dikaji secara bersamaan pada penelitian-penelitian sebelumnya. Dengan demikian, RPS hasil rekonstruksi menjadi lebih relevan, sistematis, dan siap mendukung pembelajaran berbasis proyek yang berorientasi pada Outcome-Based Education.